Shikonin Inhibits the Proliferation of Human Breast Cancer Cells by Reducing Tumor-Derived Exosomes - Yao Wei; Mingzhen Li; Shufang Cui; Dong Wang; Chen-Yu Zhang; Ke Zen; Limin Li (Molecules, 2016)
Shikonin is a naphthoquinone isolated from the traditional Chinese medicine Lithospermum. It has been used in the treatment of various tumors. However, the effects of shikonin on such diseases have not been fully elucidated. In the present study, we detected the exosome release of a breast cancer cell line (MCF-7) with shikonin treatment and found a positive relationship between the level of secreted exosomes and cell proliferation. We next analyzed miRNA profiles in MCF-7 cells and exosomes and found that some miRNAs are specifically sorted and abundant in exosomes. Knockdown of the most abundant miRNAs in exosomes and the MCF-7 proliferation assay showed that miR-128 in exosomes negatively regulates the level of Bax in MCF-7 recipient cells and inhibits cell proliferation. These results show that shikonin inhibits the proliferation of MCF-7 cells through reducing tumor-derived exosomal miR-128. The current study suggests that shikonin suppresses MCF-7 growth by the inhibition of exosome release.